PERAN PENGETAHUAN PRODUK HALAL DAN RELIGIUSITAS TERHADAP KEPUTUSAN PEMBELIAN MELALUI KESADARAN LABEL HALAL - Muhammad Romi Dian Sukma; Budhi Cahyono (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2021)
This study aims to analyze the role of halal product knowledge and religiosity in purchasing decisions for halal label products through awareness of halal labels. The population in this study were consumers who often consume halal food and beverage products in Kabupaten Semarang. The type of data collection method used was purposive sampling, then the questionnaire was distributed to 100 respondents who consumed halal foods and drinks. Based on the results of the data analysis studied, it can be concluded that halal product knowledge and religiosity had a significant positive effect on halal label awareness and purchase decisions of halal products, and awareness of halal labels also had a significant positive effect on purchasing decisions for halal products. Meanwhile, the halal label awareness variable was able to mediate between knowledge of halal products and religiosity on purchasing decisions for halal products.